2020
DOI: 10.1093/ejcts/ezaa010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of minimally invasive extracorporeal circulation on coagulation—a randomized trial

Abstract: OBJECTIVES Minimally invasive extracorporeal circulation (MiECC) is suggested to have favourable impact on blood loss compared to conventional extracorporeal circulation. We aimed to compare the impact of both systems on coagulation. METHODS Randomized trial comparing endogenous thrombin-generating potential early after elective coronary surgery employing either MiECC group (n = 30) or conventional extracorporeal circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The current study is a substudy of the "Miniaturized Extracorporeal Circulation Study" (ClinicalTrials.gov ID: NCT03216720). 12 Patients over 40 years of age referred for elective isolated CABG by the multidisciplinary Heart Team at Aarhus University Hospital, Denmark, were eligible for inclusion. Exclusion criteria were reduced ejection fraction (<40%), severe renal impairment (eGFR <30 mL/min/1.73 m 2 or dialysis), history of coagulopathy, abnormal platelet count (<100 or >450 10 9 /L), active participation in another intervention trial, and female of child-bearing potential without negative pregnancy test.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is a substudy of the "Miniaturized Extracorporeal Circulation Study" (ClinicalTrials.gov ID: NCT03216720). 12 Patients over 40 years of age referred for elective isolated CABG by the multidisciplinary Heart Team at Aarhus University Hospital, Denmark, were eligible for inclusion. Exclusion criteria were reduced ejection fraction (<40%), severe renal impairment (eGFR <30 mL/min/1.73 m 2 or dialysis), history of coagulopathy, abnormal platelet count (<100 or >450 10 9 /L), active participation in another intervention trial, and female of child-bearing potential without negative pregnancy test.…”
Section: Study Populationmentioning
confidence: 99%
“…3 Perioperative management, surgery, MiECC, and CECC circuit have been described in detail previously. 12…”
Section: Surgery and Clinical Managementmentioning
confidence: 99%
“…Despite heparinization, both TAT and F1 þ 2 have been found highly elevated in patients undergoing cardiopulmonary bypass, indicating ongoing thrombin formation during surgery. [144][145][146] Ex vivo thrombin generation capacity has further been found decreased in the postoperative phase, indicated by prolonged lag time and low ETP and peak thrombin formation compared with healthy individuals. 147 This indicates excessive prothrombin consumption and decreased hemostatic capacity, which may enhance bleeding risk in the early postoperative phase.…”
Section: Thrombin Generation and Bleedingmentioning
confidence: 99%
“…[149][150][151] Our group found that high intraoperative TAT and F1 þ 2, but not decreased ETP, was associated with a higher number of blood transfusions. 144 Thus, assessment of thrombin generation Table 1 Markers of thrombin generation and thromboembolic risk in various clinical conditions…”
Section: Thrombin Generation and Bleedingmentioning
confidence: 99%
See 1 more Smart Citation